A Head-Mounted Multi-Camera System for Electrophysiology and Behavior in Freely-Moving Mice - Sattler, Nicholas J.; Wehr, Michael (Frontiers in Neuroscience, 2021)
Advances in the ability to monitor freely-moving mice may prove valuable for the study of behavior and its neural correlates. Here we describe a head-mounted multi-camera system for mice, comprised of inexpensive miniature analog camera modules. We illustrate the use of this system with several natural behaviors including prey capture, courtship, jumping, and exploration. With a four-camera headset, monitoring the eyes, ears, whiskers, rhinarium, and binocular visual field can all be achieved simultaneously with high-density electrophysiology. With appropriate focus and positioning, all eye movements can be captured, including cyclotorsion. For studies of vision and eye movements, cyclotorsion provides the final degree of freedom required to reconstruct the visual scene in retinotopic coordinates or to investigate the vestibulo-ocular reflex in mice. Altogether, this system allows for comprehensive measurement of freely-moving mouse behavior, enabling a more holistic and multimodal approach to investigate ethological behaviors and other processes of active perception.